Features of the American model of cooperative stores on distribution of grain - Самойленко, Т. В. (Scientific Progress & Innovations, 2012)
The features of the American model of cooperative stores on distribution of grain were considered. Existing local, regional, interregional and international cooperative stores that are engaged in grain agricultural business were analyzed. The basic ways of development of grain-growing marketing stores, reasons of their merger and consolidation in conditions of modern financial and economic crisis were explained, the analysis of the economical growth of the cooperative stores, that are situated in the middle zone of the USA was conducted. It is established that, for the expansion of their scope of activity and strengthening of their market power, cooperative stores develop joint ventures or joint agency markets.